The Internal/External Frame of Reference Model of Self-Concept and Achievement Relations: Age-Cohort and Cross-Cultural Differences - Marsh, Herbert W.; Abduljabbar, Adel Salah; Parker, Philip D.; Morin, Alexandre J. S.; Abdelfattah, Faisal; Nagengast, Benjamin; Möller, Jens; Abu-Hilal, Maher M. (American educational research journal, 2015)
The internal/external frame of reference (I/E) model and dimensional comparison theory posit paradoxical relations between achievement (ACH) and self-concept (SC) in mathematics (M) and verbal (V) domains; ACH in each domain positively affects SC in the matching domain (e.g., MACH to MSC) but negatively in the nonmatching domain (e.g., MACH to VSC). This substantive-methodological synergy based on latent variable models of Trends in International Mathematics and Science Study (TIMSS) data supports the generalizability of these predictions in relation to: mathematics and science domains, intrinsic motivation as well as self-concept, and age and nationality, based on nationally representative matched samples of fourth- and eighth-grade students from three Middle Eastern Islamic, five Western, and four Asian countries (N=117,321 students) with important theoretical, developmental, cross-cultural, and methodological implications.